Książki celebrytów, czyli pisarze, gwiazdy i literatura - Kasperek, Kinga (Śląskie Studia Polonistyczne, 2014)
The author focuses on connections between literature and celebrities. The text opens with recalling the problem of absence of literature in the media and the popularity of celebrity-written books. Subsequently, the author recalls examples of writer attempts to appear in the media by assuming functions of a columnist or a celebrity. She explains the celebrity mechanism (quoting texts by Przemysław Czapliński, Dariusz Nowacki, and Wiesław Godzic) and points to celebrity aspirations of some writers, who aim to increase the popularity of their books. Later, she focuses on books written by celebrities, their memoirs and guides; she analyzes and interprets self-help books by Krzysztof Ibisz and Katarzyna Cichopek. While utilizing theories by Pierre Bourdieu, media experts and conclusions drawn from the analysis of these texts, she determines that celebrity books feature short sales cycles and tabloid content. It is important to relate to the author’s personal experiences, and the goal of these books is to constantly remind the readers of themselves in order to remain in the public sphere. A book becomes a kind of a fetish – it’s not the content that counts, but the mere fact of existing, which causes the celebrity to become a writer, thus sanctioning their presence in the media and increasing the sales of a product (which is the celebrity himself). A perfect example of this phenomenon is Ilona Felicjańska and her book Wszystkie odcienie czerni, which was to change the model’s image and prove her talent. This publication and its reception is the subject of an analysis, which shows that readers are not eager to accept such changes, and an aspiring writer becomes a Girard-esque scapegoat.